Penerapan Pelayanan Publik Berbasis Kebutuhan Kelompok Rentan pada Pelayanan Administrasi Kependudukan di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pringsewu - Silvia Silvia Silvia; Nana Mulyana; Apandi Apandi (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2026)
Every citizen has the right to inclusive and equitable public services, including vulnerable groups such as people with disabilities, the elderly, and pregnant women. This study examines the implementation of the principle of public services that are friendly to vulnerable groups in the civil registration administration at the Pringsewu Regency Population and Civil Registration Office and identifies the factors hindering it. The study employs a qualitative case study approach with data collection through interviews, observations, and document reviews. The analysis is based on eight principles outlined in Ministerial Regulation PANRB No. 11 of 2024, including equality of rights, accessibility, professionalism, accountability, transparency, participation, and protection from violence. The research results indicate that the agency has provided accessibility facilities, priority service counters, specialized assistance, and outreach services. However, implementation remains constrained by budget limitations, suboptimal outreach efforts, a shortage of staff with specialized competencies, technical disruptions, and low participation of vulnerable groups in the formulation of service policies.